Shifting Cultures and Motivations: Transforming identity through modifying interior worlds. - Smith, Nicola Dawn (Black Swan Press, 2013)
Attending to the fabric of the house through maintenance or modification, and accommodating the shifting desires and requirements of family is a life-long commitment to home making that many people make when buying property. Several generations may witness the life span of the same family home, accommodating them through changing eras and changing economies. These domestic buildings age and morph and intertwine with the changing lives of the inhabitants, the successive fashions in home décor and increasing pressures to remain efficient and functional, such as accommodating new technologies. When there is no practical need for a homeowner to reconfigure their physical environment, such as requiring additional space to accommodate an expanding family, other shifting cultural and behavioural pressures can provoke action. This paper will draw on a current doctoral research study to explore aspects of personal and social motivation underlying the changes we make to our homes, and our lives.